THE ROLE OF STAKEHOLDERS IN UNPLANNED TOURISM BUSINESS AT TASIKMALAYA REGENCY - M. Indra Gunawan; Tutut Sunarminto; Adjat Sudrajat (Acitya: Jurnal Vokasi Bisnis Digital, Akuntansi Lembaga Keuangan Syariah dan Usaha Perjalanan Wisata, 2023)
The state of tourism activities in Tasikmalaya Regency has fluctuated. The fluctuations that occur include the number of tourist visits, as well as the number of tourist sites. There are tourist objects that are not legal and have not been recorded, grew from the initiative of tourists or the community, and are not yet well established in their management which is then referred to as unplanned tourism business. This study examines the role of stakeholders with their various interests and various dynamics. The support for these facilities and services involves many other parties who have their respective roles, functions, and/or interests. The process of accommodating stakeholders is possible to have an impact on the development of unplanned tourism business in Tasikmalaya Regency. Based on the research results, internal stakeholders ensure that the unplanned tourism business from internal factors of business development and sustainability aspects runs optimally. Meanwhile, external stakeholders are supporting parties and play a role in ensuring that external factors of business development take sides and are in line with the vision of developing unplanned tourism business in accelerating procedures to become an established and legal ecotourism and in accordance with sustainability aspects (ecological aspects, social aspects, and environmental aspects). economy).